Transgene verification and technical improvement in the establisment of transgenic miR-32 mouse line - Kakkonen, Maija (2015)
The main challenge to be faced with prostate cancer (PCa) is the segregation and treatment of patients with life-threatening disease. As current prognostic, diagnostic and therapeutic tools are insufficient, solution is tried to be found from new biomarkers. One of these could be microRNA miR-32, which is possible up-regulated target of androgen receptor in aggressive PCa. Btg2 and Klf2 have further been suggested to be potential down-regulated miR-32 targets. To study hypothesized miR-32 oncogenicity in vivo, transgenic mice over-expressing miR-32 specifically in the prostate are established. Establishment of transgenic mouse line is a prolonged process, in which transgene functionality needs to be verified. Additionally, more than one so called founder line needs to be created from the same gene construct to confirm the phenotype. At the time of this study one line with verified miR-32 expression was established and more founder lines were screened for. In the first part of this study, transgene functionality i.e. expression and its effect on possible target genes was examined with quantitative PCR in the prostate samples of one new founder line. In the second part of this study, the suitability of PaxGene method for future studies was piloted. Molecular fixative PaxGene was used for the first time for prostate fixation in a desire to preserve both tissue morphology and integrity of nucleic acids from the same sample enabling one prostate to be used for both histopathological examination and molecular analyses. Traditionally these have been done from different prostates, as morphology preserving fixation methods have degraded RNA. Molecular analyses have further been done separately from different prostate lobes. In the one prostate method not only financial benefits but also ethical improvements would be achieved, as mouse individuals can be spared. Importantly, the transgene-phenotype conclusions would be more reliable too. To study PaxGenes feasibility, its RNA preservation ability was assessed by surveying the RNA integrity with BioAnalyzer. In addition, as the whole prostate cross-section with different lobes and adjacent tissues were now included in the RNA extraction as well, different tissue and prostate markers were used to study the possible effects of these issues on transgene detection. Clear transgene expression was detected only in two samples, whereas in rest of the samples the expression was of low level. Further, down-regulation of neither Btg2 nor Klf2 was observed in the transgenic samples. However, the RNA integrity PaxGene provided was on the same sufficient level that the traditional Trizol method constantly provides. Prostate marker expression profiles reveal that varying prostate lobe ratios may affect to transgene detection and be the reason for the low transgene expression values. However, prostate adjacent tissues most likely do not disturb the detection. It is also highly possible that the PaxGene procedure itself does not have an influence, but instead transgene is silenced. As a conclusion, PaxGene is a possible choice of method for future studies, if constant transgene detection can be verified even with varying prostate lobe ratios. PaxGene provides sufficient intact RNA and thus it could be possible used in in situ-hybridization based expression detection as well. In any case, not all the transgenic samples here have the desired transgene over-expression and thus it can not be verified that the transgene functions properly. For this reason, additional samples need to be examined in subsequent founder lines. Only with verified transgene over-expression reliable conclusions of the connections between the transgene and PCa can be made. In addition, possible down-regulation of Btg2 and Klf2 should be examined again in subsequent samples, before any final conclusions of their role as miR-32 targets are made.